Harmonization of Human Reproduction with Islamic Law: A Review of Legal Aspects in the Context of the Development of Reproductive Technology - Putri Suci Ramadiah; Oryza Sativa H. Sihotang; Irwansyah Irwansyah (LPPM UIKA Bogor, 2024)
Human reproduction is a very important process and is related to Islamic law. In this case, Islam's role is as a moral and ethical foundation that influences the way humans handle reproduction. Several aspects related to the legal aspects of human reproduction are cloning reproduction, test tube babies and abortion. The aim of this research is to determine the legal aspects of human reproduction by connecting them with theories related to Islamic law. This research method uses descriptive qualitative with literature study methods to analyze data taken from books, national journal articles and other literature. The research results show that IVF, reproductive cloning and abortion are things that can be done with the provisions that have been made and do not violate religious and legal norms.